2020
DOI: 10.3389/fvets.2020.570593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics BaSC06 on Intestinal Digestion and Absorption, Antioxidant Capacity, Microbiota Composition, and Macrophage Polarization in Pigs for Fattening

Abstract: This study aimed to compare the effects of BaSC06 and antibiotics on growth, digestive functions, antioxidant capacity, macrophage polarization, and intestinal microbiota of pigs for fattening. A total of 117 pigs for fattening with similar weight and genetic basis were divided into 3 groups: Anti group (containing 40 g/t Kitasamycin in the diet), Anti+Ba group (containing 20 g/t Kitasamycin and 0.5 × 10 8 CFU/kg BaSC06 in the diet) and Ba group (containing 1 × 10 8 cfu/Kg BaSC06 in the diet without any antibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…The BA can also improve the digestive enzyme activity of intestinal tract chyme after being ingested by animals. Research on pigs indicates that dietary BA supplementation increased the activities of trypsin, amylase, and lipase in the chyme of duodenum and jejunum of growing-finishing pigs and piglets ( Hu et al, 2018 ; Cao et al, 2020 ). However, reports on the effect of BA on the digestive enzyme activity of broilers are very limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BA can also improve the digestive enzyme activity of intestinal tract chyme after being ingested by animals. Research on pigs indicates that dietary BA supplementation increased the activities of trypsin, amylase, and lipase in the chyme of duodenum and jejunum of growing-finishing pigs and piglets ( Hu et al, 2018 ; Cao et al, 2020 ). However, reports on the effect of BA on the digestive enzyme activity of broilers are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be assumed that the digestion and utilization of nutrients in diets could be increased then the growth performance is improved by supplementation BA. The increase of digestive enzyme activities may be due to the secretion of BA, and the stimulation of endogenous enzyme synthesis by BA in the intestines ( Hu et al, 2018 ; Cao et al, 2020 ). Additionally, dietary BA also may improve enzyme levels by perfecting intestinal morphology and integrity ( Lei et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies performed by Dayong Ren [ 31 ] and A. de Moreno de LeBlanc [ 32 ] displayed that long-term probiotic administration could increase the phagocytosis ability and M1 polarization of peritoneal macrophages. Additionally, Cao et al [ 33 ] reported that oral Bacillus amyloliquefaciens 06 administration could simultaneously enhance the protein expression of M1 and M2 polarization marker, iNOS , Arg and CD206 (mannose receptor) in ileum mucosa. Moreover, emerging evidence demonstrated that probiotics could exert an anti-inflammatory effect on maintaining immune homeostasis through regulating the conversion of macrophage polarization when the host is under pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization defines probiotics as live microorganisms that confer a health benefit to the host when administered in adequate amounts. In addition, probiotics can effectively promote the health and growth of host animals by regulating the balance of microorganisms in the intestinal tract, enhancing the barrier function of intestinal epithelial cells, inhibiting the growth and adhesion of pathogenic microorganisms, and regulating immunomodulatory effects ( Bubnov et al, 2015 ; Hu et al, 2017 ; Cao et al, 2020 ). Lactic acid bacteria are the most common probiotics and have been widely used and considered safe for humans and animals ( Slattery et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%